Population pharmacokinetics of recombinant factor VIII:C (ReFacto®) in adult HIV-negative and HIV-positive haemophilia patients. - Karafoulidou A; Suarez E; Anastasopoulou I; Katsarou O; Kouramba A; Kotsi P; Zografidis A; Lukas JC (European Journal of Clinical Pharmacology, 2009)
PURPOSE: The aim of this study was to explore possible differences in the pharmacokinetics (PK) of recombinant factor VIII:C (ReFacto - ReFacto ) in HIV+ vs. HIV- patients and also differences in the chromogenic substrate bioassay (CHS) and one-stage clotting (OSC) methods. METHODS: Twenty-eight haemophilia A adults (20 HIV- and eight HIV+) were assayed with both the CHS and OSC methods. An average of two and six samples were collected per patient for HIV-/+, respectively, after one, and occasionally two more, prophylactic doses (mean 2,003 IU; range 1,000-4,300 IU). The observations were analysed with the mixed-effects (population) compartmental PK modelling package NONMEM (nonlinear mixed-effects modelling) and the FOCE (first-order conditional estimation) method. Base modelling was performed independently for the CHS and OSC bioassays for comparison, and covariate models and simulation tests were done only for the commonly used OSC bioassay. The final covariate model was validated using the bootstrap method. Monte Carlo simulations were used to estimate the expected probability of exceeding 20%, 40% or 60% of normal factor VIII:C in plasma after a single dose, corresponding to required levels for preventing mild, moderate and life-threatening haemorrhages. RESULTS: One-compartment base-model population PK parameters were [mean parameter (interpatient variability %)] for CHS: clearance (CL) = 2.56 dl h(-1) (33.2%); volume of distribution (V) = 34.8 dl (12.8%); and for OSC: CL = 3.83 dl h(-1) (47.8%), V = 53.7 dl (22.4%). The volumes differed significantly between the CHS and OSC methods (p < 0.0001), and variabilities were higher for OSC. Nevertheless, the empirical half-lives (t(1/2) = l n (2) x V/CL) were similar for CHS and OSC, [(mean +/- standard deviation (SD)], 9.5 +/- 3 h and 10.2 +/- 4 h, respectively. In covariate modelling with the OSC-derived model, HIV status (VIR) was a significant categorical predictor (p < 0.005) for V. The final covariate models with OSC were for CL = 3.93 + 0.09 x (WT-75) and for V = 48.6 x (1 + 0.36 x VIR) + 0.55 x (WT-75); therefore, V for the typical HIV+ patient was 36% higher than for the HIV- patient. CONCLUSIONS: Both HIV- and HIV+ patients showed 100% success with the 20% threshold at doses >20 IU/kg. HIV- patients receiving >50 IU/kg had a 100% expected chance of success for all thresholds. HIV+ patients for moderate or life-threatening haemorrhage treatment need 10 IU/kg more than the HIV- patient equivalent to have the same probability of success.